3D nanomaterial silica aerogel via diffusion of chiral compound driven broadband reflection in chiral nematic liquid crystals. Issue 6 (3rd May 2019) - Chen, Qi; Wang, Dong; Gao, Hong; Zhang, Jingjing; Xing, Yan; Yang, Zhou; Cao, Hui; He, Wanli
ABSTRACT: In the study, a novel method of broadening the bandwidth by fabricating the silica aerogel film composited with the chiral nematic liquid crystal (N*-LC) is proposed. Diffusion of chiral compound filled in the silica aerogel resulted in the non-uniform pitch distribution, which can be anchored by UV-radical polymerisation. The results strongly suggested that the reflection bandwidth could be broadened preferably by adjusting the silica aerogel condensation time, the content of UV polymerisable free radical monomer and the polymerisation temperature. The reflection bandwidth was broadened from 270 nm to 878 nm, and the centre wavelength was blue-shifted by 642 nm. A general correlation among the silica aerogel condensation time, the polymerisation condition, and the reflective region will be outlined. Graphical Abstract: